UPAYA GURU DALAM MENGATASI KESULITAN MOTIVASI BELAJAR SISWA SELAMA PANDEMI COVID-19 DI SD - Yusnan, Muh (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2022)
Schools are currently limited to face-to-face learning, by implementing online learning, due to the Covid-19 pandemic which is a key factor in the challenges in the education sector. This study aims to describe the efforts of teachers in overcoming students' learning motivation in elementary schools during the pandemic covid-19. This study uses a type of field research (field research) with a descriptive qualitative approach. The technique used in this research is the technique of observation, interviews, and documentation. Data analysis in this study includes data reduction, data display, and conclusion/verification. The results of this study indicate that (1) the efforts made to overcome the difficulties of students' learning motivation in participating in learning during the covid-19 pandemic in class IV are by holding meetings with students three times a week, providing encouragement and motivation, and collaborating with parents. (2) The factors that cause student learning difficulties in participating in learning during the covid-19 pandemic are due to factors, school facilities and infrastructure, low family economy, and parental factors.